INCOME AS A SOURCE AND FACTOR OF HUMAN CAPITAL ACCUMULATION - Коровина, Н. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The article examines the impact of dynamics in the welfare of population on the changes in individual and aggregate human capital in transitional economy. The institutional aspects of the relationship between household income and motivation of population economic activity is analyzed.